THE AMNESTY OF POLITICAL PARTIES AS AN OBSTACLE TO FLEXIBLE AND PLURAL LAW IN THE IMPLEMENTATION OF PUBLIC POLICIES FOR WOMEN'S PARTICIPATION IN POLITICS - Muller Franqui, Luiz Paulo; Fernandes Neto, Raimundo Augusto; Rohrbacher, Laísa (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
The Constitutional Amendment No. 133 of 2024 reflects a legislative history of exempting political parties from complying with public policies aimed at promoting minority candidacies. This article analyzes the state's resistance in enforcing laws that encourage representation, with a focus on women's participation. Although legislation has advanced, such as the inclusion of gender quotas, its effectiveness is undermined by amendments that exempt parties from responsibilities for failing to meet these obligations. The Superior Electoral Court has been a significant actor in promoting these policies but faces barriers resulting from amendments that hinder the practical implementation of the measures. The study reflects on the crisis of representation and the need for an effective constitutional culture that goes beyond the formality of laws and incorporates democratic values of inclusion. The true effectiveness of public policies depends on the commitment of the state and political parties to promoting a more plural and inclusive representative democracy.
Keywords: political participation; female representation; party amnesty; public policies; pluralism